Improving the competence of School Health Unit Teachers in first aid for wounds and choking at SDN Lamklat, Aceh Besar [Peningkatan kompetensi guru uks dalam pertolongan pertama luka dan tersedak di SDN Lamklat Aceh Besar] - Uci Nurcahaya; Arfiza Ridwan (Buletin Pengabdian Bulletin of Community Services, 2025)
Ensuring a safe and health-promoting school environment requires adequate teacher competence in first aid management. However, limited teacher knowledge and practical skills in providing first aid remain a critical concern in many elementary schools. This community service initiative aimed to implement community nursing care through educational interventions and first aid demonstrations focusing on injury and choking management, thereby improving teachers knowledge and preparedness. The activity employed the community nursing process comprising assessment, diagnosis, planning, implementation, and evaluation. A windshield survey revealed frequent minor injuries among students, insufficient first aid facilities, the absence of a School Health Unit (UKS), and several environmental risk factors for injuries. Interviews with the principal and UKS instructor indicated that while injuries were common and choking incidents had occurred within the past six months, teachers had not previously received formal training or procedural guidance. The intervention included lectures and demonstrations delivered to three UKS instructor teachers, utilizing PowerPoint slides, leaflets, teaching aids, and guidebooks. Knowledge and skills were evaluated using pre-test and post-test instruments and an observation checklist. Results indicated a substantial increase in knowledge from 33.3% to 100%, with wound management skills rated as good (100%) and choking management skills rated as good in most participants (66.7%). In conclusion, educational and demonstrative interventions effectively enhanced teachers first aid competence. The program has potential for replication by schools, community health centers, and education authorities as a promotive and preventive strategy at the elementary school level.